2017
DOI: 10.1002/mds.27173
|View full text |Cite
|
Sign up to set email alerts
|

Profiling novel metabolic biomarkers for Parkinson's disease using in‐depth metabolomic analysis

Abstract: Objective To profile the amine/phenol submetabolome to determine potential metabolite biomarkers associated with Parkinson’s disease (PD) and PD with incipient dementia. Methods At baseline of a 3-wave (18-month intervals) longitudinal study, serum samples were collected from 42 healthy controls and 43 PD patients. By wave 3 (year 3) 16 PD patients were diagnosed with dementia and were classified as PD with incipient dementia at baseline. Metabolomic profiling using dansylation isotope labeling liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 40 publications
5
85
0
Order By: Relevance
“…Therefore, many studies focused on metabolic biomarker screening (comparing healthy subjects with either familial PD or idiopathic PD), for an early detection of potential development of PD. The metabolic profiles of PD patients (in cerebrospinal fluid (CSF), blood or urine) usually reflect oxidative stress [24,[27][28][29][30][31] or mitochondrial dysfunction [24,[31][32][33][34][35]. However, many studies also observed differences in metabo-lites from bacterial origin, which are summarized in Table 2.…”
Section: Altered Bacterial-derived Metabolites In Patients With Parkimentioning
confidence: 99%
“…Therefore, many studies focused on metabolic biomarker screening (comparing healthy subjects with either familial PD or idiopathic PD), for an early detection of potential development of PD. The metabolic profiles of PD patients (in cerebrospinal fluid (CSF), blood or urine) usually reflect oxidative stress [24,[27][28][29][30][31] or mitochondrial dysfunction [24,[31][32][33][34][35]. However, many studies also observed differences in metabo-lites from bacterial origin, which are summarized in Table 2.…”
Section: Altered Bacterial-derived Metabolites In Patients With Parkimentioning
confidence: 99%
“…Metabolomics (Nicholson et al 1999;Nicholson et al 2002;Patti et al 2012), as a methodology of measuring 'dynamic multi-parametric metabolic response of living systems to pathophysiological stimuli or genetic modification', has been extensively applied to PD research in the past decade (Hatano et al 2016;Shao and Le 2019). However, most of the studies focused on identifying early diagnostic biomarkers in cerebrospinal fluid or blood (Bogdanov et al 2008;Trezzi et al 2017;Han et al 2017). Here, in order to examine the feasibility of metabolomics-driven therapeutic target identification for PD, metabolic changes in the striatum of LPS-plus-MPTPinduced PD mouse model were dissected using a mass spectrometry-based metabolomics strategy.…”
mentioning
confidence: 99%
“…Classical studies addressing CSF and serum/plasma concentrations of amino acids in PD patients have been largely inconclusive and have shown high variability, which may be related with several factors such as sample size, differences in the handling and storage of samples or in the study methodologies, the lack of a control group or adequate matching between PD patients and controls, and differences in antiparkinsonian therapies [1]. In recent years, there has been an increasing interest in the potential of proteomics/metabolomics multi-analyte profiles both in CSF [3][4][5][6] and/or in serum/plasma [3,[5][6][7][8][9][10][11][12][13][14] to discriminate PD patients from controls.…”
Section: Introductionmentioning
confidence: 99%